On the applicability of some existing tropospheric scintillation prediction models for Ikeja and Abuja, Nigeria - Adeyemo, Zachaeus Kayode; Yusuf, Ridwan Olalekan; Lasisi, Hammed Oyebamiji; Ojo, Samson Iyanda; Omowaiye, Rebecca Olufunmilayoa; Adedeji, Adebukola Ayoade (Institute of Advanced Engineering and Science, 2022)
Tropospheric scintillation which causes rapid fluctuation of signal due to the turbulence in the atmosphere is of significance in satellite link budget design. Existing models that predict the intensity of scintillation such as Karasawa, International Telecommunication Union Radiocommunication (ITU-R) Sector, Otung, Van de Kamp and Ortgies are not appropriate for predicting scintillation intensity (SI) in Nigeria due to localization of the models to particular regions. The monthly average air temperature and relative humidity for Ikeja and Abuja, Nigeria, retrieved from the Nigerian Meteorological Centre data bank were used for the investigation. An elevation angle of 5° was used as look angle, antenna diameter of 0.3 m, 40 GHz and 45 GHz frequencies were considered in this study. The existing scintillation model values were then compared with the measured values for the two locations to determine the best performance model. The SI results at 40 GHz and 45 GHz were obtained for each of the existing models. It could be deduced from the results obtained that orgies model values were the most closet to the measured values. Therefore, Orgies-N model was the most appropriate for SI prediction in Ikeja and Abuja.